2021
DOI: 10.3390/jcm10204689
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endoscopic Sinus Surgery on Eustachian Tube Function in Adult Sinusitis Patients: A Prospective Case-Control Study

Abstract: The eustachian tube (E-tube) function is known to be related with sinusitis; however, the effect of endoscopic sinus surgery (ESS) on E-tube function is not clearly documented. This study aimed to prospectively evaluate the function of the E-tube by using both subjective and objective tests in adult chronic sinusitis patients undergoing ESS, and to compare with those of the patients without sinusitis. Thirty adult patients who underwent ESS for treatment of chronic sinusitis and another thirty patients without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…6,7 In support of this hypothesis, previous several studies demonstrated that the dysfunction of the Eustachian tube was correlated with increased sinonasal symptoms and, it was common in patients with CRS who need endoscopic sinus surgery, and the symptoms resolved after the surgery. 8,9 Moreover, consistent with our study, one cohort study described a significantly higher subsequent development of cholesteatoma in CRS patients during an 8-year follow-up period than in controls. 10 The present study provided several meaningful clinical implications.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…6,7 In support of this hypothesis, previous several studies demonstrated that the dysfunction of the Eustachian tube was correlated with increased sinonasal symptoms and, it was common in patients with CRS who need endoscopic sinus surgery, and the symptoms resolved after the surgery. 8,9 Moreover, consistent with our study, one cohort study described a significantly higher subsequent development of cholesteatoma in CRS patients during an 8-year follow-up period than in controls. 10 The present study provided several meaningful clinical implications.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, we hypothesized that the dysfunction of the Eustachian tube due to CRS could contribute to the development of cholesteatoma, since the relationship between Eustachian tube dysfunction and cholesteatoma has been clearly stated 6,7 . In support of this hypothesis, previous several studies demonstrated that the dysfunction of the Eustachian tube was correlated with increased sinonasal symptoms and, it was common in patients with CRS who need endoscopic sinus surgery, and the symptoms resolved after the surgery 8,9 . Moreover, consistent with our study, one cohort study described a significantly higher subsequent development of cholesteatoma in CRS patients during an 8‐year follow‐up period than in controls 10 …”
Section: Discussionsupporting
confidence: 88%
“…25,26 Although this prospective study demonstrated the 1-year outcomes of ETD in CRS patients following ESS, additional detailed objective studies of ETD should be performed. Choi et al 23 found significant improvement in Eustachian tube function after ESS in the right Valsalva test, right deflation test, and left deflation test. Bowles et al 17 and Chen et al 24 found type A tympanograms were increased postoperatively.…”
Section: Discussionmentioning
confidence: 98%
“…From the initial 120 consecutive CRS patients evaluated, 28 patients were excluded due to history of pharyngeal or ear surgeries (three), history of radiotherapy in head and neck region (two), and incomplete follow-up intervals (23). Finally, 92 CRS patients were prospectively enrolled and completed all follow-up evaluations at 3-month intervals during the 1-year study period.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The included studies were reviewed and extracted as follows: the author, year of publication, number of ears examined for MEP and ETF, diagnosing tools used to evaluate ETF, procedures and questionnaires to evaluate MEP, follow-up period after septoplasty, outcomes, and conclusions. The excluded studies were as follows: where patients underwent endoscopic sinus surgery only, 13) where patients with NSD underwent no septoplasty or other MEP tests except tympanogram, [14][15][16] insufficient data on MEP or ETF, 7,[17][18][19] and full text written by other languages than English. We evaluated the risk of bias of the studies included in the meta-analysis based on the Newcastle-Ottawa Scale criteria and Cochrane Handbook for Systematic Review of Interactions, and all included studies showed good or fair quality.…”
Section: Study Recordsmentioning
confidence: 99%